Diabetic Exudate Detection in Color Retinal Images - Ali, Dalia (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2019)
Diabetic retinopathy is a vascular complication of long-term diabetes. It causes damage to the small blood vessels positioned in the retina. These damaged blood vessels affect the macula and lead to vision loss. Exudates are one of the early signs of diabetic retinopathy disease in the retinal image, which occurs due to built-up of lipidic accumulation within the retina. In this paper, an image processing method is presented for diabetic exudates detection. First, high performance pre-processing is applied not only for de-noising and normalization but also to remove artefacts and reflection that could mislead exudates detection. Then, morphological operations are applied for the final candidate segmentation. Eight region features are extracted from the exudate region then random forest classifier is applied to differentiate between exudates and non-exudates region. The proposed method is evaluated using e_ophtha_EX dataset, achieving 80% sensitivity and 77% positive predicted value.